齿轮箱故障诊断技术的新发展 - 高国华; 张永忠 (Jixie chuandong)
Gearbox is the important transmission component in the mechanical equipments, so much attention has been given to the fault diagnosis technology for it. This article introduces several new signal analysis methods and fault diagnosis technologies and their applications.